2017
DOI: 10.1002/pbc.26708
|View full text |Cite
|
Sign up to set email alerts
|

Complete durable response of a pediatric anaplastic oligodendroglioma to temozolomide alone: Case report and review of literature

Abstract: Anaplastic oligodendroglioma (AO) is rare in children. Treatment typically consists of varying combinations of surgery, chemotherapy, and radiotherapy. We present a pediatric case of frontal lobe AO with periventricular subcallosal extension and local leptomeningeal involvement. The isocitrate dehydrogenase (IDH) wild-type tumor was MGMT methylated and contained an ATRX mutation, BRAF alteration, and 1p/19q co-deletion; a combination of alterations mostly encountered in pediatric oligodendrogliomas. The patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
0
3
0
2
Order By: Relevance
“…On the treatment of glioma according to the current classification, low grade gliomas with a poor prognosis, most cases were IDH wildtype, should receive more intensive treatment, especially in triple-negative gliomas. However, high grade gliomas with good prognosis factors, such as having 1p/19q codeletion, could appropriately use conservative management without radiation in some cases, rather than the typical treatment consisted of varying combinations of surgery, chemotherapy, and radiotherapy, which was recently, to some extent, confirmed by Sorge C et al [59], for they found a WHO III anaplastic oligodendroglioma with IDH wildtype and 1p/19q codeletion in a children only underwent a near total resection and had a complete, durable response to temozolomide alone. Meanwhile, we also need to focus on triple-negative gliomas, for they account a relatively high proportion in our Chinese cohort.…”
Section: Discussionmentioning
confidence: 91%
“…On the treatment of glioma according to the current classification, low grade gliomas with a poor prognosis, most cases were IDH wildtype, should receive more intensive treatment, especially in triple-negative gliomas. However, high grade gliomas with good prognosis factors, such as having 1p/19q codeletion, could appropriately use conservative management without radiation in some cases, rather than the typical treatment consisted of varying combinations of surgery, chemotherapy, and radiotherapy, which was recently, to some extent, confirmed by Sorge C et al [59], for they found a WHO III anaplastic oligodendroglioma with IDH wildtype and 1p/19q codeletion in a children only underwent a near total resection and had a complete, durable response to temozolomide alone. Meanwhile, we also need to focus on triple-negative gliomas, for they account a relatively high proportion in our Chinese cohort.…”
Section: Discussionmentioning
confidence: 91%
“…Інші вчені вважають, що ризик діагностики гліоми у пацієнтів, які раніше отримували ліку вання від іншого неопластичного захворюван ня, починає знижуватися через 15-20 років, наближаючись до ризику загальної популяції населення [42]. Гліоми характеризуються знач но вищою злоякісністю та гіршим прогнозом [40,41,42,57]. Особливо несприятливим він є при вторинних злоякісних гліомах у дітей.…”
Section: матеріал і методи дослідженняunclassified
“…Інші вчені вважають, що ризик діагностики гліоми у пацієнтів, які раніше отримували ліку вання від іншого неопластичного захворюван ня, починає знижуватися через 15-20 років, наближаючись до ризику загальної популяції населення [42]. Гліоми характеризуються знач но вищою злоякісністю та гіршим прогнозом [40,41,42,57]. Особливо несприятливим він є при вторинних злоякісних гліомах у дітей.…”
Section: матеріал і методи дослідженняunclassified